Loss-of-function mutations in QRICH2 cause male infertility with multiple morphological abnormalities of the sperm flagella - Ying Shen (Nature Portfolio, 2019)
Multiple morphological abnormalities of the sperm flagella (MMAF) is a cause of male infertility. Here the authors identify homozygous nonsense mutations of the glutamine rich 2 (QRICH2) gene in two MMAF patients from 2 consanguineous families and show using QRICH2 knockout mice that the protein is required for sperm flagellar formation and motility.